A case study exploring the influence that management policy and motivational strategies have on employees within a Durban restaurant - Beeput, Diajal (The IIE, 2017)
Owing to the current state of the South African economy and the country’s unemployment rate, employees endure harsh business practises to secure employment, leading to demotivation and reduced performance. The restaurant industry is missing a chance to improve staff motivation and performance, and therefore to improve their business. Another problem is that those staff members are faced with potentially abusive treatment in their workplace. The aim of the study was to explore the influence that management policy and motivational strategies have on employee motivation and performance. The sample for this study was three individuals employed at a particular Durban restaurant. The study showed that management policies and motivational strategies negatively influence motivation and performance. Recommendations for future research include a larger sample size, conducted across various restaurants, to improve reliability and trustworthiness of the findings. Further research can also aim to explore the illegal practices used by restaurants and how this influences motivation and performance.
Keywords: Unemployment; South African economy; Staff performance; Employee motivation